Voluntary Social Reporting: An Iso-Beta Portfolio Analysis. - Anderson, John C.; Frankle, Alan W. (The Accounting Review, 1980)
Abstract ABSTRACT: In recent years, there has been an increasing interest in the communication and reporting by large corporations on their social performance. Most of the attention has been devoted to either the need or the appropriate mode for corporate social disclosure. This study attempts to assess the impact of the capital markets of the social disclosure that already exists on a voluntary basis. The returns to portfolios composed of securities of socially disclosing firms are compared to the returns to portfolios of equivalent (systematic) risk composed of securities of non-disclosing firms. The findings indicate that social disclosure has information content and that the market values this disclosure positively.